Eventos climáticos extremos : a homogeneização da comunidade aquática pela seca em escala local. - Bertoncin, Ana Paula dos Santos (2017)
Extreme hydrological events tend to become frequent together with global warming and promote changes in species composition and dominance. Thus, we used benthic macroinvertebrates to test the hypothesis that drought events determine local biotic homogenization in shallow floodplain lakes. We took sediment samples in three sampling areas of shallow floodplain lake during reference months, a normal hydrological cycle, and during a prolonged drought in an atypical hydrological cycle. Our findings indicate that species density, richness and diversity increased during the droughts. However, community composition significantly differed between reference and drought periods, in which only species adapted to unfavorable environmental conditions occurred. Beta diversity measured spatially during the reference and drought periods was significantly different, with lower centroide distances in the drought period. Then, in scenarios of climate change with frequent extreme events, we expect that droughts may cause negative impacts on aquatic communities, leading to biotic homogenization. Moreover, our findings indicate that prolonged droughts could increase the time needed to community recovery, suggesting low resilience. Therefore, increasing frequency of extreme drought events may promote an alternative community structure and potentially generate a community structure regime shift.